Hydrochemical Assessment of Groundwater around Lapite Dumpsite for Irrigation Water Quality in Ibadan, Southwestern Nigeria - Oluwatoyin Opeyemi Akintola; Gabriel Oladapo Adeyemi; Adewunmi Idayat Bodede; Oluwatoyin Oluwatoyin Adekoya; Kekinde O. Babatunde (Journal of Bioresource Management, 2021)
Due to the increase in population and industrialization growth, most countries in the world depend on groundwater to meet agriculture demands for food production. The increase in water contamination due to indiscriminate solid wastes has necessitated the assessment of water quality and its suitability for agricultural usage. Twenty four groundwater and ten stream water samples were randomly collected from the downslope and upslope side of the dumpsite for all the major physio-chemical parameters. The pH of water samples indicates slightly acidic to alkaline in nature. High concentrations of nitrate, total dissolved solids and electrical conductivity suggest the impact of the waste on the water resource. Assessment of irrigation water quality based on Sodium Adsorption Ratio (SAR), Soluble Sodium Percentage (SSP), Permeability Index (PI) and Magnesium content (MC) indicated that most of the water samples fall within the permissible standard for irrigation water. Thus, the water should be used with caution on crops for long time agricultural sustainability.